PENGARUH DUKUNGAN KELUARGA TERHADAP KEPATUHAN MINUM OBAT PASIEN HIPERTENSI DI PUSKESMAS MUARA WIS - Sri Endah Handayani; Husnul Warnida; Triswanto Sentat (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
One of the public health concerns is drug non-adherence. The main cause of poor hypertension control is noncompliance with antihypertensive medications. The elements that drive compliance behavior are numerous and complicated, with social support being one of them. Family support is critical in health care since it is through family support that a healthy family can be achieved. Family members can help by providing information about their sickness or reminding them to take their medications. The goal of this research was to identify the relationship between family support and medication adherence in hypertensive patients at Muara Wis Health Center, Kutai Kartanegara Regency, Province East Borneo. This study is descriptive correlational and uses a cross-sectional method, which involves measuring or observing at the same time and the same location. The participants in this study were 100 hypertensive patients of Muara Wis Health Center. The data in this study were analyzed using Spearman rank correlation. Based on the MMAS (Morisky Medication Adherence Scale) questionnaire, medication adherence in hypertensive patients at the Muara Wis Health Center had 52 percent low adherence, 29 percent moderate adherence, and 19 percent high adherence. According to pill count, low adherence patients was 51 percent, moderate adherence was 29 percent, and high adherence was 20 percent. Patients with hypertension who had poor family support were 54 percent, those who received moderate family support were 26 percent, and those who received strong family support were 20 percent. Hence, there is a significant relationship between family support and medication adherence in hypertensive patients of Muara Wis Health Center.